Implementing Jigsaw IV Technique to Improve the Eleventh Grade Students' Narrative Text Reading Comprehension Achievement - Zuraida, Anisa Ulya; Andayani T, Made Adi; Wahjuningsih, Eka (English Education Study Program, 2016)
This classroom action research was intended to improve the eleventh grade students' participation and reading comprehension achievement of narrative text by implementing Jigsaw IV Technique at SMA Plus Darul Hikmah. Purposivemethod was used to choose the research area and the research subject. The primary data were collected by using observation and reading test. The supporting data were collected by interview and documentation. Both the results of observation and the reading test were analyzed statistically by using percentage formula. The students’ participation in Cycle 1 was 53% and in Cycle 2 was 82%. Meanwhile, the result of students’ reading achievement in Cycle 1 was 59% and in Cycle 2 was 82%. It means that the implementation of Jigsaw IV Technique could improve the students’ participation and reading comprehension achievement. Therefore, it is suggested to implement Jigsaw IV Technique to improve the students’ participation and reading comprehension achievement.